(untitled) (Medico Legal Update, 2020)
Cost Sharing is a fee payable by the patient participant of the social insurance administration Organization because it gets health services in the hospital which is derived from the reduction in tariffs with the amount of costs incurred by the social insurance administration Organization. Analyse the additional costs that the Passo Hative Hospital has done to patient satisfaction. This type of research is quantitative research by using a cross-sectional design approach. The population in this study is all the patients of the national health care insurance not the recipient of dues are being treated at hospitalisation in the Passo Hative Hospital in Ambon City with the last one month visit was 150 patients. The sampling techniques in this study are accidental sampling. The results showed there was an additional cost relationship moving the treatment class to patient satisfaction (P = 0.001). There is a relationship of medical services additional costs to patient satisfaction (P = 0,016) and there is a connection to the additional cost of medication to patient satisfaction (P = 0,000) of the hospital as a service provider of the social insurance administration Organization in order to be more observant to see the cause of the users of the social insurance administration Organization to change the treatment class of the care and fulfill and complement medical services and medicines that are the right of the patient according to the social insurance administration Organization.